1998
DOI: 10.1073/pnas.95.15.8449
|View full text |Cite
|
Sign up to set email alerts
|

Transition state structure of arginine kinase: Implications for catalysis of bimolecular reactions

Abstract: Arginine kinase belongs to the family of enzymes, including creatine kinase, that catalyze the buffering of ATP in cells with f luctuating energy requirements and that has been a paradigm for classical enzymological studies. The 1.86-Å resolution structure of its transition-state analog complex, reported here, reveals its active site and offers direct evidence for the importance of precise substrate alignment in the catalysis of bimolecular reactions, in contrast to the unimolecular reactions studied previousl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

13
368
0

Year Published

2000
2000
2016
2016

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 239 publications
(381 citation statements)
references
References 50 publications
13
368
0
Order By: Relevance
“…HTK Prediction of the three-dimensional structure by Swiss Model indicated that the structure of Siphonosoma HTK is very similar to that of Limulus AK (data not shown), whose crystal structure has been determined [25].…”
Section: Structural Basis For Catalytic Properties Of Siphonosomamentioning
confidence: 99%
“…HTK Prediction of the three-dimensional structure by Swiss Model indicated that the structure of Siphonosoma HTK is very similar to that of Limulus AK (data not shown), whose crystal structure has been determined [25].…”
Section: Structural Basis For Catalytic Properties Of Siphonosomamentioning
confidence: 99%
“…The three-dimensional structure of Sabellastarte AK2 was generated by SWISS-MODEL based on the TSAC structures of Limulus AK and Torpedo CK, both of which have a similar substrate-binding site [14,15]. Then we estimated the position of the substrate arginine in Sabellastarte AK2 by overlapping the position of L-arginine in the TSAC structure of Limulus AK (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…2). While this residue does not appear to be directly involved in substrate binding in the TSAC structures of CK and AK, it is located close to the guanidine substrate-binding site [14,15]. Site-directed mutagenesis studies of this residue using rabbit CK and Einenia LK have shown that it has a significant effect on enzymatic activity and guanidino substrate specificity [20,21].…”
Section: Amino Acid 89mentioning
confidence: 99%
See 1 more Smart Citation
“…6 Although the crystal structures of several vertebrate creatine kinases are currently available, only a single AK has been structurally characterized so far, that of Limulus polyphemus (Horseshoe crab) AK. 7 We have previously characterized the molecular and biochemical characterization of the T. cruzi AK (TcAK) 8,9 and we report here the crystal structure of the ligand-free (open form) of the enzyme at 1.9 Å resolution.…”
Section: Introductionmentioning
confidence: 99%